Impact of timing on surgical outcome in patients with cauda equina syndrome caused by lumbar disc herniation - Hakija Bečulić; Rasim Skomorac; Aldin Jusić; Fahrudin Alić; Melica Imamović; Alma Mekić-Abazović; Alma Efendić; Harun Brkić; Amir Denjalić (Medicinski glasnik, 2016)
Aim: To analyze the relationship between timing of surgery and outcome in patients with cauda equina syndrome caused by lumbar disc herniation. Methods: A retrospective, non-randomized clinical study included 25 consecutive patients with cauda equina syndrome (CES) caused by lumbar disc herniation. All patients were operated within 24 hours after hospitalization at the Department of Neurosurgery, Cantonal Hospital Zenica, Bosnia and Herzegovina, between January 2000 and December 2010. All patients were evaluated before surgery on the basis of complete history, neurological examination and neuroimaging evaluations using CT (computed tomography) and MRI (magnetic resonance imaging). Results: Statistically significant difference between preoperative and postoperative bladder (p=0.05) and bowel (p=0.05) function was found. A significant number of patients had bladder and bowel recovery after surgery, nine (36%) and 11 (44%), respectively. Significant recovery of muscle strength was noted with complete recovery (5/5) in 12 (48%) and partial recovery in 13 (52%) patients. Complete sensory recovery was noted in 16 (64%), incomplete in four (16%), and in five (20%) patients there were no changes. Most commonly, patients with complete sensory recovery were operated within 48 hours of symptom onset. In most patients early surgery was associated with better outcome. Conclusion: This research showed that early decompression correlated with better outcome. Patients with cauda equina syndrome must be cleared for surgery in optimal conditions and, if it possible within optimal timing for recovery (within 48 hours).
Keywords: sphincter dysfunction; early decompression; recovery